KAJIAN KEAKURATAN DATA AERONAUTICAL INFORMATION PUBLICATION (AIP) VOLUME I GENERAL AND EN-ROUTES DI INDONESIA - Meldi G; Endang Sugih Arti.; Norman Dani (Politeknik Penerbangan Indonesia Curug, 2019)
This study aims to know the conditions and constrains faced in maintaining the accuracy of AIP Indonesia’s data Volume I General and Enroute in Indonesia. This research conducted at JATSC LPPNPI Jakarta. Research methods used is descriptive and data collection methods are interviews and library studies.